Gain of Function Recyclable Photoswitches: Reversible Simultaneous Substitution and Photochromism Generation - Zitzmann, Max; Fröhling, Matthias; Dube, Henry (Angewandte Chemie International Edition, 2024)
The use of molecular photoswitches has spread to virtually every field of pure and applied chemistry because of the extraordinary level of control they provide over the behavior of matter at the smallest scales. Photoswitches possess at least two different states with distinct structures and/or electronics and further functionalization of their core chromophore structures is needed to tailor them for a specific application. In this work we present a different concept for the generation and use of molecular photoswitches. It allows not only simultaneous establishment of photochromism and functionalization, but also full recyclability of a non-photochromic precursor material. Using a high-yielding and reversible ammonium salt formation, a functional group is introduced into a symmetric precursor while at the same time a strong electronic push-pull character is established in the structure. The resulting desymmetrization leads to efficient photoswitching capacity and the functional group can be fully removed subsequently by a simple heating step recovering the precursor for another functionalization round. We finally demonstrate feasibility of this concept over two consecutive closed loop functionalization/photoswitching/recovery steps. This concept offers great potential in any chemical research and application driven area but especially for the creation of responsive reprogrammable materials, no-background photoswitch labeling, and sustainable chemistry.
CRIS-Team Scopus Importer:2024-03-08
Keywords: gain of function; photochromes; photoswitch; recycling; reversible functionalization